The Intergroup Rhabdomyosarcoma Study Group (IRSG): Major Lessons From the IRS-I Through IRS-IV Studies as Background for the Current IRS-V Treatment Protocols. (2001) - Raney, R. Beverly; Maurer, Harold M.; Anderson, James R.; Andrassy, Richard J.; Donaldson, Sarah S.; Qualman, Stephen J.; Wharam, Moody D.; Wiener, Eugene S.; Crist, William M.
Abstract : Purpose. To enumerate lessons from studying 4292 patients with rhabdomyosarcoma (RMS) in the Intergroup Rhabdomyosarcoma Study Group (IRSG, 1972–1997). Patients. Untreated patients < 21 years of age at diagnosis received systemic chemotherapy, with or without irradiation (XRT) and/or surgical removal of the tumor. Methods. Pathologic materials and treatment were reviewed to ascertain compliance and to confirm response and relapse status. Results. Survival at 5 years increased from 55 to 71% over the period. Important lessons include the fact that extent of disease at diagnosis affects prognosis. Re-excising an incompletely removed tumor is worthwhile if acceptable form and function can be preserved. The eye, vagina, and bladder can usually be saved. XRT is not necessary for children with localized, completely excised embryonal RMS. Hyperfractionated XRT has thus far not produced superior local control rates compared with conventional, once-daily XRT. Patients with non-metastatic cranial parameningeal sarcoma can usually be cured with localized XRT and systemic chemotherapy, without whole-brain XRT and intrathecal drugs. Adding doxorubicin, cisplatin, etoposide, and ifosfamide has not significantly improved survival of patients with gross residual or metastatic disease beyond that achieved with VAC (vincristine, actinomycin D, cyclophosphamide) and XRT. Most patients with alveolar RMS have a tumor-specific translocation. Mature rhabdomyoblasts after treatment of patients with bladder rhabdomyosarcoma are not necessarily malignant, provided that the tumor has shrunk and malignant cells have disappeared. Discussion. Current IRSG-V protocols, summarized herein, incorporate recommendations for risk-based management. Two new agents, topotecan and irinotecan, are under investigation for patients who have an intermediate or high risk of recurrence.